Pre-mobilisation of neutrophils from acute exercise-induced muscle damage: potential implications for short-term vaccination responses, satellite cell dynamics and skeletal muscle recovery - Rawlins, Maia (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.